Serum Neurofilament Light Chain Measurement in MS: Hurdles to Clinical Translation - Thebault, Simon; Booth, Ronald A.; Rush, Carolina A.; MacLean, Heather; Freedman, Mark S. (Frontiers in Neuroscience, 2021)
Measurement of serum neurofilament light chain concentration (sNfL) promises to become a convenient, cost effective and meaningful adjunct for multiple sclerosis (MS) prognostication as well as monitoring disease activity in response to treatment. Despite the remarkable progress and an ever-increasing literature supporting the potential role of sNfL in MS over the last 5 years, a number of hurdles remain before this test can be integrated into routine clinical practice. In this review we highlight these hurdles, broadly classified by concerns relating to clinical validity and analytical validity. After setting out an aspirational roadmap as to how many of these issues can be overcome, we conclude by sharing our vision of the current and future role of sNfL assays in MS clinical practice.